Hydrographic and bathymetric features of the Ostional National Wildlife Refuge and adjacent areas, Guanacaste, Costa Rica - Brenes-Rodríguez, Carlos L. (2012)
Between February 6 and 11, 2012, a hydrographic cruise and bathymetric sounding were conducted in the region located between Guiones and Cuajiniquil, in the Northern Pacific area of Costa Rica. The range of surface temperatures is 25.5 to 27.5°C, and the saline surface ranges between 33.2 and 33.8 PSU. The thermocline is located at 20 m at the northern end of the region, while at the southern end, from Ostional up to Guiones, it was observed slightly deeper, approximately 25 m deep. The thickness of the mixed layer was 10 m in virtually all the studied area. Two gyres, one cyclonic and another anticyclonic, were observed in front of Ostional. The surface layers were occupied by the Surface Tropical Water (STW), with salinities below 34 PSU and temperatures greater than 26°C, and the intermediate levels (~ 50 m) by the Subsurface Subtropical Water (SSW), characterized by a saline core near 35 PSU. The bathymetry of the region shows isobaths parallel to the coast, with an elevation close to 20 m deep at the southern end of this area. The degree of inclination did not exceed 14.5°.